Efektivitas Pengajaran Kosakata Pada Siswa Kelas Sepuluh Di SMK Darul Huda Tahun Sekolah 2022/2023 Menggunakan Permainan Scrabble - Khoiriah, Siti Zulfa Muhlishotul; Widyaningsih, Titik Lina (EduCurio: Education Curiosity, 2023)
This research is aimed to find out the effect of teaching vocabulary mastery through Scrabble game. This research was a quantitative research with quasi- experimental design. The population of this research is all of the tenth grade students of SMK Darul Huda in the academic year of 2022/2023. The researcher used purposive sampling. The sample of this study was X TKR A and X TKR B. The instrument of this research were vocabulary tests (Pre-Test and Post-Test). In analyzing the data, the researcher used the Independent-samples test in the IBM SPSS Statistics 25 program for windows. The results showed that the student who are taught using Scrabble game have significantly better vocabulary mastery than those who are taught using conventional method. This is evidenced from the significant values of 0.000 < 0.05 which means there are significant difference on student vocabulary mastery of those who are taught using scrabble game and who are taught using conventional method. Based on the results of the study, it can be concluded that Scrabble game have significant effect toward vocabulary mastery.